Pelatihan Pengolahan Makanan Lokal untuk Peningkatan Gizi dan Pendapatan Keluarga di Desa Pantai Labu - Mahdiah Mahdiah; Ida Nurhayati; Zuraidah Nasution (Syntax Idea)
Pantai Labu Pekan Village, Pantai Labu District, Deli Serdang Regency, is one of the villages whose area is located on the coast. According to the research conducted, there are still toddlers who experience stunting and malnutrition, the low coverage of poverty, and the low knowledge of pregnant women in toddlers causes the growth and development of toddlers to be disrupted and this can affect their health status broadly. The purpose of this research is to apply science and technology to the community to increase knowledge and skills in the health sector, form/develop community groups in the health sector, apply research results to improve public health for the welfare of public health. This research is observational research with a descriptive research design. The research was conducted in June 2023 in Pantai Labu Pekan Village, Pantai Labu District. In this Community Service activity, the methods carried out were training in local pagan-based snack food processing for pregnant women and WUS and conducting demonstrations on making sukahitu cookies, moringa leaves, fish nuggets, fish sandwiches, rebon shrimp crackers and satay donuts. This program to increase the knowledge of pregnant women and wus starts from 4 stages, namely licensing, preparation, implementation and evaluation. The results of community service activities are that there is an increase in the knowledge of pregnant women and WUS about snack foods which can help in efforts to deal with stunting and there is an increase in the knowledge of pregnant women and WUS about snack foods. From snack foods that are highly nutritious to prevent stunting and snacks containing moringa leaves as a way to overcome anemia and breast milk production.